Functional Importance Of Psychological Protection In The Person (Texas Journal of Multidisciplinary Studies, 2022)
Psychological protection is a complex structure and is manifested in a simpler and supreme order of behavior. Theoretical psychological protection is divided into two types: basic psychological protection and acquired (secondary) psychological protection. The main purpose of psychological protection is to eliminate psychological disability in a person.